2022
DOI: 10.1038/s41467-022-29449-4
|View full text |Cite
|
Sign up to set email alerts
|

Bridging the gap between atomically thin semiconductors and metal leads

Abstract: Electrically interfacing atomically thin transition metal dichalcogenide semiconductors (TMDSCs) with metal leads is challenging because of undesired interface barriers, which have drastically constrained the electrical performance of TMDSC devices for exploring their unconventional physical properties and realizing potential electronic applications. Here we demonstrate a strategy to achieve nearly barrier-free electrical contacts with few-layer TMDSCs by engineering interfacial bonding distortion. The carrier… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 40 publications
0
25
0
1
Order By: Relevance
“…Recently, as shown in Figure 6h, Cai et al reported an atomically sharp edge interface between semiconducting and semimetallic MoS 2 . [102] The semi-metallic feature originates from the distorted octahedral structure of MoS 2 formed by a plasma treatment. The semi-metallicity and sharp interfacial edge without noticeable defects lead to an ideal and barrier-free electrical interface.…”
Section: Top-down Phase Engineeringmentioning
confidence: 99%
See 4 more Smart Citations
“…Recently, as shown in Figure 6h, Cai et al reported an atomically sharp edge interface between semiconducting and semimetallic MoS 2 . [102] The semi-metallic feature originates from the distorted octahedral structure of MoS 2 formed by a plasma treatment. The semi-metallicity and sharp interfacial edge without noticeable defects lead to an ideal and barrier-free electrical interface.…”
Section: Top-down Phase Engineeringmentioning
confidence: 99%
“…[21] TMD-based FETs also exhibited high mobility, high current density, and low R C with 1D edge contacts. [39,78,102] Such 2D FETs are expected to facilitate a 3D integration of vertically stacked multifunctional devices such as memory, logic, and sensor devices, with potential for usage in in-memory and in-sensor computing systems. [81] Further, the 1D edge contacts can lead to unique electrical features in FET device structures that have been challenging to achieve using typical top contacts, such as Fermi level depinning, immunity to contact scaling, and in-plane anisotropic transport.…”
Section: Device Applications With Edge Contactsmentioning
confidence: 99%
See 3 more Smart Citations